2001
DOI: 10.1161/hq1001.097780
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Size and Atherosclerosis Susceptibility in Apoe −/− and Ldlr −/− Mice

Abstract: Abstract-Two hypercholesterolemic mouse models, the apo-E-deficient mouse (Apoe Ϫ/Ϫ ) and the LDL receptor-deficient mouse (Ldlr Ϫ/Ϫ ), have been used extensively as animal models of atherogenesis. Total plasma cholesterol levels in chow-fed Apoe Ϫ/Ϫ mice are much higher than in Ldlr Ϫ/Ϫ mice. In a recent study, we managed to even-up the cholesterol levels in Apoe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 27 publications
3
49
0
1
Order By: Relevance
“…Although both b-VLDL and LDLs carry cholesterol in circulation, they are not equally atherogenic once deposited in the arterial intima. 23 b-VLDLs are large in size and contain more apoB-48 in postprandial state, whereas small-sized LDLs contain more apoB-100. In light of such physical and chemical differences between the two particles, one can envision that small-sized LDLs are more atherogenic because these small LDLs may enter the intima more easily and may be more susceptible to oxidation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although both b-VLDL and LDLs carry cholesterol in circulation, they are not equally atherogenic once deposited in the arterial intima. 23 b-VLDLs are large in size and contain more apoB-48 in postprandial state, whereas small-sized LDLs contain more apoB-100. In light of such physical and chemical differences between the two particles, one can envision that small-sized LDLs are more atherogenic because these small LDLs may enter the intima more easily and may be more susceptible to oxidation.…”
Section: Discussionmentioning
confidence: 98%
“…20,21 Studies using genetically modified animals have revealed that remnant lipoproteins and LDLs are actually different in terms of atherogenicity. 22,23 Although LPL is protective against cholesterol-diet-induced atherosclerosis in LDL receptor and apoE KO mice, 6,7 studies of these mice did not demonstrate a significant increase of small LDLs in LPL transgenic animals and thus failed to provide a clear answer about whether LPL-generated small LDLs are atherogenic.…”
mentioning
confidence: 99%
“…Possible explanations for the more aggressive disease in SR-uPA ϩ/0 Apoe Ϫ/Ϫ mice despite plasma cholesterol levels similar to those of SR-uPA ϩ/0 Ldlr Ϫ/Ϫ mice include the lack of apoE-mediated reverse cholesterol transport, absence of the anti-oxidant and anti-inflammatory activities of apoE, (43)(44)(45) and earlier onset hyperlipidemia in Apoe Ϫ/Ϫ mice. The increased longevity of SR-uPA ϩ/0 Ldlr Ϫ/Ϫ mice versus SR-uPA ϩ/0 Apoe Ϫ/Ϫ mice allowed us to quantify uPA-accelerated atherosclerosis over a more extended time course, providing clues to the mechanisms of uPA/Plg-accelerated atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite the high correlation between apoB 100 and non-HDL-C, these parameters reflect different biological entities. 30 Thus, non-HDL cholesterol may not be an adequate surrogate for apoB 100 .…”
Section: Discussionmentioning
confidence: 99%